Synthesis and Hypoglycemic Activity of Some New Flavone Derivatives 2nd Communication: 4’-Flavonyl-2,4-thiazolidinediones - Bozdağ, Oya; Verspohl, Eugen J; Ertan, Rahmiye (Arzneimittelforschung, 2000)
A new series of 4’-flavonyl-2,4-thiazolidinedione, 2,4-imidazolidinedione and 2-thiohydantoin derivatives (1-10) were synthesized. Their chemical structures have been elucidated by IR, 1H-NMR, mass spectra and elementary analysis. The synthesized compounds were tested for their insulinotropic effects in INS-1 cells. Inhibitory effects were observed for compounds 1, 2, 6 and 7.
Keywords: Antidiabetic agents; Diabetes mellitus, insulin secretion; Flavone derivatives; 2,4-Thiazolidinediones